2005
DOI: 10.1159/000083920
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Genotypes of Hepatitis G Virus among Hemodialysis Patients in Eastern Anatolia, Turkey

Abstract: Objectives: To study the prevalence and genotype distribution of hepatitis G virus (HGV) in hemodialysis patients in East Anatolia, Turkey. Subjects and Materials: Eighty-nine hemodialysis patients and 30 healthy individuals were analyzed by using reverse-transcriptase nested polymerase chain reaction with primers specific for 5′ untranslated region. HGV genotyping was performed by PCR and three randomly selected HGV-positive samples were sequenced. Results: Of the 89 hemodialysis patients, HGV RNA was detecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 45 publications
1
14
0
3
Order By: Relevance
“…Previous studies revealed that GBV-C genotype 1 was prevalent mainly in Ghana, Zaire and West Africa; genotype 2 in the USA, Spain, Egypt, Nepal, Thailand, India, Turkey, Saudi Arabia, Pakistan, UAE and Myanmar; genotype 3 in Japan, Philippines and Bolivia; genotype 4 in Vietnam, Myanmar and Cambodia; genotype 5 in South Africa [Smith et al, 1997;Naito et al, 1999;Al-Ahdal et al, 2000;Tucker and Smuts, 2001;Abraham et al, 2002;Abu Odeh et al, 2005;Ozdarendeli et al, 2005] and genotype 6 in Indonesia [Handajani et al, 2000;Muerhoff et al, 2006]. Phylogenetic analysis of our samples revealed that all GBV-C isolates were genotype 2, and classified as subtype 2a.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies revealed that GBV-C genotype 1 was prevalent mainly in Ghana, Zaire and West Africa; genotype 2 in the USA, Spain, Egypt, Nepal, Thailand, India, Turkey, Saudi Arabia, Pakistan, UAE and Myanmar; genotype 3 in Japan, Philippines and Bolivia; genotype 4 in Vietnam, Myanmar and Cambodia; genotype 5 in South Africa [Smith et al, 1997;Naito et al, 1999;Al-Ahdal et al, 2000;Tucker and Smuts, 2001;Abraham et al, 2002;Abu Odeh et al, 2005;Ozdarendeli et al, 2005] and genotype 6 in Indonesia [Handajani et al, 2000;Muerhoff et al, 2006]. Phylogenetic analysis of our samples revealed that all GBV-C isolates were genotype 2, and classified as subtype 2a.…”
Section: Discussionmentioning
confidence: 98%
“…Kan ve kan ürünleri ile parenteral yolla bulaşabilen hepatit G ve TTV prevalansının hemodiyaliz hastalarında sağlıklı bireylerden daha yüksek olduğu bildirilmiştir [12][13][14][15][16][17].…”
Section: Discussionunclassified
“…Hemodiyaliz hastalarında hepatite neden olan hepatit E (HEV), Hepatit G (HGV) , transfüzyonla bulaşan virus (TTV) viruslerinin sıklığına ilişkin çeşitli çalışmalar yapılmıştır ve Transfusion transmitted virus (TTV)'un bulaş yolu tam olarak aydınlatılamasa da, hemodiyaliz hastalarında TTV seroprevalansı %9,3-83 arasında değişmektedir [3][4][5][6][7][8][9][10][11][12][13].…”
Section: Introductionunclassified
See 1 more Smart Citation
“…These conflicting results may be related to various factors such as the GBV‐C/HGV infection rate in the general population, the size of the study group, the methods used to detect the GBV‐C/HGV, and the demographic and clinical features of the patients (23). Regarding HD patients, the HGV prevalence ranges from 3% to 57% in transversal studies (15,24–26). In a preliminary report from Iran, a rate of 28.6% of GBV‐C infection was reported among a group of patients (chronic hepatitis, kidney transplant, and volunteer blood donors).…”
Section: Discussionmentioning
confidence: 99%